Fatigue life estimation of additive manufactured parts in the as‐built surface condition. Issue 3 (11th February 2019) - Pegues, Jonathan W.; Shamsaei, Nima; Roach, Michael D.; Williamson, Randall S.
Abstract: In this study, a simple approach for estimating the effect of surface roughness on the fatigue strength of additive manufactured Ti‐6Al‐4V is investigated. Surface roughness parameters are used to estimate the elastic stress concentration factor and the resulting fatigue stress concentration factor. The estimated fatigue strengths are then compared with experimentally obtained fatigue strengths for specimen batches with varying surface conditions. Results show that the estimated fatigue strengths are comparable with the experimental fatigue strengths, and the predicted stress‐life curves fit the experimental data reasonably well.